Streptomyces Strains Promote Plant Growth and Induce Resistance Against Fusarium verticillioides via Transient Regulation of Auxin Signaling and Archetypal Defense Pathways in Maize Plants - Tran, Trang Minh; Ameye, Maarten; Devlieghere, Frank; De Saeger, Sarah; Eeckhout, Mia; Audenaert, Kris (Frontiers in Plant Science, 2021)
Driven by climate change, Fusarium ear rot (FER) caused by Fusarium verticillioides occurs more frequently in maize worldwide. In parallel, legislative regulations and an increasing environmental awareness have spurred research on alternative FER biocontrol strategies. A promising group of bacterial control agents are Streptomyces species in view of their metabolic versatility. However, insights into the molecular modes of action of these biocontrol agents are often lacking. This study aims at unraveling the biocontrol efficacy of Streptomyces rhizobacterial strains against F. verticillioides. We first assessed the direct antagonism of four Streptomyces strains ST02, ST03, ST07 and ST08. Then, a profile of 16 genes associated with intrinsic plant defence signalling was assessed in maize plants. Both in-vitro and in-vivo data showed that the biocontrol strain ST03 perfectly suppressed the growth of F. verticillioides. High inhibition efficacy was also observed for extracellular compounds in the supernatant secreted by this strain. Especially, on maize cobs, the biocontrol strain ST03 not only inhibited the proliferation of F. verticillioides but also significantly repressed the fungal fumonisin production at 7 days after inoculation. On maize plants, the direct antagonism was confirmed by a significant reduction of the fungal DNA level in soils when co-applied with F. verticillioides and strain ST03. In terms of its action on plants, strain ST03 induced a downregulation of auxin responsive genes (AUX1, ARF1 and ARF2) and gibberellic acid (GA)-related gene AN1 even in absence of F. verticillioides at early time points. Especially, in leaves, the biocontrol strain induced the expression of genes related to the salicylic acid (SA), and 2,4-dihydroxy-7-methoxy-1,4-benzoxazin-3-one (DIMBOA)-mediated pathways, and pathogenesis-related proteins in presence or absence of the pathogen. Interestingly, the biocontrol strain significantly promoted plant growth even in presence of F. verticillioides. All of which demonstrated that the Streptomyces strain ST03 is a promising FER biocontrol and a growth-promoting candidate.